Transformation of Prayer Time Schedules: from A Static-Passive to A Dynamic-Variative Perspective - Riza, Muhammad Himmatur; Djamaluddin, Thomas; Izzuddin, Ahmad (Universitas Islam Sultan Agung, 2022)
Prayer times are extremely important for Muslims, as they serve as a guide for the beginning of prayer times. However, there are still people who do not fully understand the impact of changes in the position of the Sun, which causes the start of prayer times to change daily. Additionally, some people still use perpetual prayer time schedules. Although they use the term